Peripheral neuropathies in Waldenström's macroglobulinaemia. Issue 2 (17th January 2006) - Levine, T; Pestronk, A; Florence, J; Al-Lozi, M T; Lopate, G; Miller, T; Ramneantu, I; Waheed, W; Stambuk, M; Stone, M J; Choksi, R
Abstract : Objective: We sought to determine the prevalence, clinical features, and laboratory characteristics of polyneuropathies in Waldenström's macroglobulinaemia (WM), a malignant bone marrow disorder with lymphocytes that produce monoclonal IgM. Methods: We prospectively studied 119 patients with WM and 58 controls. Medical history was taken, and neurological examinations, electrodiagnostic tests, and serum studies were performed by different examiners who were blinded to results except the diagnosis of WM. Results: Polyneuropathy symptoms, including discomfort and sensory loss in the legs, occurred more frequently (p<0.001) in patients with WM (47%) than in controls (9%). Patients with WM had 35% lower quantitative vibration scores, and more frequent pin loss (3.4 times) and gait disorders (5.5 times) than controls (all p<0.001). Patients with IgM binding to sulphatide (5% of WM) had sensory axon loss; those with IgM binding to myelin associated glycoprotein (MAG) (4% of WM) had sensorimotor axon loss and demyelination. Patients with WM with IgM binding to sulphatide (p<0.005) or MAG (p<0.001) had more severe sensory axon loss than other patients with WM. Demyelination occurred in 4% of patients with WM with no IgM binding to MAG. Age related reductions in vibration sense and sural SNAP amplitudes were similar (∼30%) in WM and controls. Conclusions: Peripheral nerve symptoms and signs occur more frequently in patients with WM than controls, involve sensory modalities, and are often associated with gait disorders. IgM binding to MAG or sulphatide is associated with a further increase in the frequency and severity of peripheral nerve involvement. Age related changes, similar to those in controls, add to the degree of reduced nerve function in patients with WM.